MAHASISWA BERWIRAUSAHA - Firdausi Dwi Isnaini; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research analyzes the processes and networks experienced by several students from several faculties in Riau University that capable to become young entrepreneurs. The theory used in this research is the theory of social networks. This research Data is collected through observation methods and documentation. Analysis of data by using a qualitative analysis of descriptive by specifying the informant using purposive sampling. From observations in the field and identification of the research subject of six people. The results of this study have several components in the student process of entrepreneurship. Their background in opening a business is a hobby, passion, opportunities and a view of the society's lifestyle today. Work experience is also considered to have a role in encouraging student's entrepreneurial intentions. The existence of strong character such as intention to continue entrepreneurial to patience that must always take precedence to become a successful entrepreneur in the day. In the process of creating a student business has obstacles such as management of less efficient time and lack of assistance or labor. Entrepreneurial students also use social media in the marketing and development process. Social Media used are WhatsApp and Instagram. As for social networks that are intertwined to parties such as distributors, resellers also consumers are done through technology like mobile. As for network built based on network Sentiment, Power and Interest. Keywords: Entrepreneurial student, social network